En glittestok fra Dogger Banke i Nordsøen - Andersen, Søren H. (Kuml, 2005)
A flaker from the Dogger Bank in the North Sea By the end of the Ice Age, the present North Sea was dry land stretching from Denmark to the British Isles. Here, life conditions for hunter tribes must have been good and similar to those in the adjoining areas – Southern Scandinavia, Eastern England, and the Netherlands. Due to the rise of the world seas, this large land area was gradually flooded after the Ice Age, and recent geological investigations have made it possible to gain a relatively good picture of the development history of the North Sea during the last c.14000 years. These investigations show that the highest land areas – primarily the Brown Bank towards the south and the Dogger Bank towards the north – must have been large land areas far into the early Stone Age. As opposed to our geological knowledge, the archaeological finds fail to provide information about the settlement structure of the early Stone Age in this area. However, they are important because they can provide information about important issues such as when and to which extent the different land areas were flooded by the sea, and the nature of the cultural affiliations of the hunter groups living there. So far, the Stone Age finds have almost all been made in the southern part of the North Sea (Brown Bank), whereas there are just a few finds from the rest of the large sea territory. A few of these artefacts are connected to the Maglemose Culture, whereas the rest can either not be dated or are subject to the discussion whether they are actually artefacts or just products of nature. However, a new find now helps throwing light on some of these questions. It is a pressure flaker fished out of the sea at Dogger Bank, at a depth of 30 to 40 metres. The tool was made from a tine of red deer (Cervus elaphus) antler, the point of which was truncated at an angle and shows clear marks of pressure and wear (Fig. 1). In North Europe, this type of artefact is known only from the late Maglemose Culture settlements on Sea land, and it has been interpreted as a special type of pressure or percussion flaker used in connection with the production of micro-flakes (Fig. 2). Consequently, this is not a fishing tool, but an artefact type used in a settlement. In Denmark, this type of tool is dated using typology to the time between c.6700 and 6400 BC (cal.), which has later been confirmed by an AMS C14 dating giving the result of 7010 BC, or 7040-6700 BC, with one standard deviation. The find of a flaker of the late Maglemose type on Dogger Bank is important, as it shows that this part of the North Sea was still dry land about 9000 years ago. At that time, Dogger Bank was a large peninsula, situated about 100 km from both the east coast of England and the Jutland peninsula (Fig. 3). When the sea finally flooded this last piece of the original North Sea continent is more uncertain. However, geological results indicate that it happened shortly after, i.e. around 6000-5000 BC. The new find of a flaker on the Dogger Bank shows that this part of the North Sea was still dry land about 7000 BC, and that hunters and fishing groups connected to the late Maglemose Culture lived there at the time. Søren H. Andersen Nationalmuseet Translated by Annette Lerche Trolle